1977
DOI: 10.1128/aem.33.2.459-469.1977
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of cellular material from Thiobacillus ferrooxidans in the presence of organic acids

Abstract: Thiobacillus ferrooxidans cells released varying amounts of iron, phosphate, sugar, ribonucleic acid, deoxyribonucleic acid, and substances that absorb light at both 260 and 280 nm when exposed to 10-2 to 10-1 M concentrations of these organic acids: propionic, butyric, valeric, hexanoic, and oxalacetic. These acids also retarded iron oxidation by the cells. Electron microscopic observation of cells after exposure to the organic acids showed varying degrees of cell envelope disruption, suggesting that the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…6). This has been observed previously using microscopy with A. ferrooxidans grown in the presence of organic acids [13].…”
Section: Plfa Analysis and Cell Imagingsupporting
confidence: 80%
“…6). This has been observed previously using microscopy with A. ferrooxidans grown in the presence of organic acids [13].…”
Section: Plfa Analysis and Cell Imagingsupporting
confidence: 80%
“…However, membrane damage has previously been reported in bacteria after exposure to organic acid. Tuttle et al (1977) observed membrane blebbing after exposing Thiobacillus ferroodoxans to butanoic acid. Sannasiddappa thus the possibility that butanoic acid induces a similar response in A. baumannii and S. pseudintermedius cannot be discounted.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, we always observe the extracellular carbon in concentrated cultures of T. ferrooxidans to be between 15 and 22% of the total acid-stable carbon. The leakage of cellular material from T. ferrooxidans in the presence of organic acids has been documented (34). If such leakage or cell lysis were the principal source of the cell-free organic material in this case, one might anticipate that the percentage of extracellular carbon would not remain constant.…”
Section: Fig 5 In Situ Electrolytic Cultivation Of T Ferrooxidans mentioning
confidence: 99%